Argon-helium knife cryoablation plus programmed cell death protein 1 inhibitor in the treatment of advanced soft tissue sarcomas: there is no evidence of the synergistic effects of this combination therapy - Wang, Jiaqiang; Zong, Dengwei; Dong, Shuping; Gao, Shilei; Yang, Yonghao; Zhang, Peng; Wang, Xin; Yao, Weitao; Tian, Zhichao (Frontiers in Oncology, 2023)
Background: Effective treatment for advanced soft tissue sarcomas (STSs) is necessary for improved outcomes. Previous studies have suggested that cryoablation can have a synergistic effect with programmed cell death protein-1 (PD-1) inhibitor in the treatment of malignancy. This study aimed to clarify the efficacy and safety of argon-helium knife cryoablation in combination with PD-1 inhibitor in the treatment of STSs. Methods: Retrospectively collected and analyzed the clinical data of patients with advanced STS who underwent cryoablation and PD-1 inhibitor between March 2018 and December 2021. Results: This study included 27 patients with advanced STS. In terms of target lesions treated with cryoablation, 1 patient achieved complete response, 15 patients had partial response (PR), 10 patients had stable disease, and 1 patient had progressive disease. This corresponded to an overall response rate of 59.3% and a disease control rate of 96.3%. In terms of distant target lesions untreated with cryoablation, only two patients had a PR compared to the diameter of the lesion before ablation. The combination therapy was relatively well tolerated. None of the patients experienced treatment-related death or delayed treatment due to adverse events. Conclusion: Cryoablation combined with PD-1 inhibitors in the therapy of advanced STS is safe and can effectively shrink the cryoablation-target lesion. However, there is no evidence of the synergistic effects of this combination therapy.